Pengaruh Digital Marketing, Persepsi Harga, dan Brand Trust terhadap Keputusan Pembelian pada Produk Bittersweet By Najla - Saphira, Sella Deby; Anomsari, Ariati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the influence of digital marketing, price perception and brand trust on purchasing decisions for BitterSweet Najla products. This survey was conducted to all consumers who purchased BitterSweet by Najla products and to all consumers who purchased and consumed BitterSweet by Najla. Sampling was determined from a sampling method of 110 customers. The data used in this research is primary data using the data collection method of distributing questionnaires. The experiment used SPSS 25 software to analyze respondent data, test instruments, and data analysis methods such as classic hypothesis testing, multiple linear regression, t test, f test, and decision coefficients. The research results show that digital marketing has a positive and insignificant effect on the decision to purchase BitterSweet of Najla products, while price perception has a positive and significant effect on the decision to purchase BitterSweet of Najla products, and consumer trust. the brand is positive. and has a significant effect on purchasing decisions for BitterSweet Najla products. Najla Products Verdict on BitterSweet.